Entanglement entropy at large-N - P. Talavera (Journal of High Energy Physics)
Abstract I show that at early times the evaporation process for a stack of NS5-branes at high energy is suppressed in the large-N limit. At much later times, the new saddles in the gravitational action are no longer suppressed at large-N, and evaporation proceeds as usual.